Ewolucja teorii ekonomii rozwoju w XX wieku: od kategorii wzrostu gospodarczego do koncepcji zrównoważonego rozwoju - Zadroga, Adam (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2016)
The article addresses the economic theories that have arisen on the basis of development economics of the 20th century. The aim is to present the evolution of these concepts and to evaluate them. Historical, descriptive and comparative methods were used. The author argues that in face of current development issues a return to historical sources, combined with their proper reading and (re) interpretation, enables formulation of important conclusions for the present and setting more accurate targets for the future. Thanks to this reading and reinterpretation policy makers have a chance to avoid errors in managing the current socio-economic policy. The analysis led to the conclusion that (1) the understanding of economic development was at first narrowed to growth but with time has moved to (2) to the category of socio-economic development and in the 1950 s a new sub-discipline of economics - development economics - was developed. Its achievements helped to take into account in today’s prevailing approaches the social determinants of economic growth, of which sustainable development is the most popular.